Umande Trust Bio-Centre Approach in Slum Upgrading - (:unkn) unknown (My University, 2011)
The aim of this article is to present a case study of bio-centres in three slums in Nairobi: Korogocho, Kibera and Mukuru in an approach developed by Umande Trust (UT) which is seeking to improve access to basic urban services to affected communities. To-date, 49 bio-centres have also been constructed in Kisumu and Nairobi. It is hoped that this approach will attract future replication of the technology in other parts of the country. This article gives a background to the Trust and outlines the objectives, strategies, successes and challenges experienced in the course of this slum upgrading effort.
Keywords: African Research